Cellular plasticity: a double-edged sword driving malignant transformation and adaptive remodeling in stem cells - Du, Xue; Lin, Zhimei; Zeng, Yijun; Chen, Chunbao (Frontiers in Cell and Developmental Biology, 2026)
This review systematically examines the dual roles of cellular plasticity in stem cell biology. Stem cells leverage their inherent plasticity to achieve adaptive tissue remodeling, including migration, differentiation, and microenvironment interactions during development, regeneration, and homeostasis maintenance. However, this property can also be hijacked by cancer cells, particularly cancer stem cells, as a key mechanism for malignant transformation, invasion, metastasis, and therapeutic resistance. This review will delve into the molecular foundations of cellular plasticity, such as cytoskeletal dynamics, nuclear plasticity, and cell junctional plasticity, analyzing the regulatory similarities and differences between physiological remodeling and pathological transformation. Finally, we will explore the potential and challenges of targeting cellular plasticity as a novel anti-cancer strategy.